Lateral shear forces applied to cells with single elastic micropillars to influence focal adhesion dynamics - Heil, Patrick; Spatz, Joachim P. (Journal of physics. Condensed matter, 2010)
Focal adhesions (FAs) are important adhesion sites between eukaryotic cells and the extracellular matrix, their size depending on the locally applied force. To quantitatively study the mechanosensitivity of FAs, we induce their growth and disassembly by varying the distribution of intracellular stress. We present a novel method for micromanipulation of living cells to explore the dynamics of focal adhesion (FA) assembly under force. Fibroblasts are sheared laterally to their adhesion surface with single PDMS micropillars in order to apply laterally stretch or compression to focal adhesions. This allows for measuring the shear force exerted by the micropillar and correlates it with FA length and growth velocity. Furthermore, we analyze the resulting dynamics of FA molecules (paxillin) and compare intensity profiles along FAs before and after the application of external force. The responses of stretched and relaxed FAs differ fundamentally: relaxed and compressed FAs disassemble isotropically and show no length variation while stretched FAs grow unisotropically in the direction of the applied force and show protein influx only at their front.
Gesehen am 11.04.2023